2021
DOI: 10.1002/pd.5837
|View full text |Cite
|
Sign up to set email alerts
|

Uniparental disomy: Origin, frequency, and clinical significance

Abstract: Uniparental disomy (UPD) is defined as two copies of a whole chromosome derived from the same parent. There can be multiple mechanisms that lead to UPD; these are reviewed in the context of contemporary views on the mechanism leading to aneuploidy. Recent studies indicate that UPD is rare in an apparently healthy population and also rare in spontaneous abortion tissues. The most common type of UPD is a maternal heterodisomy (both maternal allele sets present). Isodisomy (a duplicated single set of alleles) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 41 publications
0
58
0
Order By: Relevance
“…In some cases, a combination of two chromosome segregation errors leads to two copies of a chromosome being inherited from a single parent, a phenomenon called uniparental disomy (UPD). A review of mechanisms for UPD can be found elsewhere in this Special Issue 12 . Similar to consanguinity, uniparental isodisomy (two identical [i.e., two homozygous] chromosomes as depicted in Figure 2) leads to an increased risk for autosomal recessive diseases in genes in the homozygous region.…”
Section: Mechanisms Leading To Chromosomal Mosaicismmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, a combination of two chromosome segregation errors leads to two copies of a chromosome being inherited from a single parent, a phenomenon called uniparental disomy (UPD). A review of mechanisms for UPD can be found elsewhere in this Special Issue 12 . Similar to consanguinity, uniparental isodisomy (two identical [i.e., two homozygous] chromosomes as depicted in Figure 2) leads to an increased risk for autosomal recessive diseases in genes in the homozygous region.…”
Section: Mechanisms Leading To Chromosomal Mosaicismmentioning
confidence: 99%
“…A review of mechanisms for UPD can be found elsewhere in this Special Issue. 12 Similar to consanguinity, uniparental isodisomy (two identical [i.e., two homozygous] chromosomes as depicted in Figure 2) leads to an increased risk for autosomal recessive diseases in genes in the homozygous region. UPD can also cause aberrant expression levels of genes that are imprinted (only expressed from one parent's chromosome and silenced on the other).…”
Section: Mechanisms Leading To Chromosomal Mosaicismmentioning
confidence: 99%
“…Benn reviews the multiple etiologic mechanisms for chromosome segregation error that can result in uniparental disomy. 29 For the non-mosaic common autosomal trisomies (21, 18 and 13), as previously noted, maternal age is the main clinical or demographic factor that pre-determines risk. However, a large number of other factors such as paternal age, exposures, and predispositions have been proposed and these are reviewed by Cuckle and Benn.…”
Section: Masset Et Al Propose That Abnormal First Zygotic Cleavage Events Inmentioning
confidence: 90%
“…The mitotic correction of the resulting aneuploid embryo (trisomy/monosomy rescue) may cause UPD. The UPD phenotypic effects may be due to the involvement of imprinting regions or isodisomy, and can result in a recessive disorder caused by a homozygous pathogenic variant that is present in only one of the parents [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%